On the Long-Time Behavior of the Thermoelastic Plates with Second Sound - Fastovska, T.B. (Журнал математической физики, анализа, геометрии, 2013)
The relation between the thermoelastic Cattaneo model and the thermoelastic Gurtin-Pipkin model is established. The existence of the compact global attractor of the Cattaneo-Mindlin plate model is proved and its properties are studied.